Strategi Pembinaan Keterampilan Kerja Yang Efektif Dalam Mengembalikan Kehidupan Warga Binaan Lembaga Pemasyarakatan Kelas II B Bondowoso - Tri Apriliana Dewi; Padmono Wibowo (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
As a state of law, Indonesia implements a criminal justice system to prosecute perpetrators of law violators. In the criminal justice process, there is a correctional sub-system that has the role of fostering lawbreakers. This coaching process is carried out by officers from the Correctional Technical Implementation Unit, especially correctional institutions. Each technical implementing unit has a different coaching strategy, although in general the coaching process implemented is based on the Correctional Law. This study aims to explain how effective job skills development strategies are in restoring the lives of reasonable fostered citizens as good and responsible citizens in Bondowoso class II B correctional institution. In this study, researchers used a qualitative approach method with a descriptive case study type with data collection techniques through interviews, observation, and documentation. The results of this study indicate that the coaching strategy applied to class II B correctional institutions is in the form of personality and independence development. However, in its implementation there are still some obstacles. Therefore, there is a need for a review of the implementation of the coaching process carried out in order to have an effective impact on the inmates in the Bondowoso Class II B Correctional Institution